Histopathological study of endometrial lesions in tertiary care hospital - Dr. Shrinivas K. Panchal; Dr. Sunil Y. Swami; Dr. Arvind. G. Valand (Tropical Journal of Pathology and Microbiology, 2017)
Objective: To study the clinico-pathological aspects and the histo-pathological patterns of endometrial lesions. Methodology: Study includes hysterectomy specimens, dilatation & curettage samples (D&C) and biopsies, received to the department of pathology. Results: Total 542 endometrial samples were received in department of Pathology during September 2013 to September 2015.Out of 542 endometrial samples, 131 are endometrial lesions. Among 131 endometrial lesions, 115 are non-neoplastic while 16 are neoplastic lesions. Most common age group for non-neoplastic lesions is 41-50 years while for neoplastic lesions it is about 51-60 years. Adenomyosis the most common (11.99%) non-neoplastic lesion while endometrioid adenocarcinoma (46.67%) ismost common neoplastic lesion. Conclusion: In present study, non- neoplastic lesions were more common out of all endometrial lesions. Among neoplastic lesions malignant lesions were more common than benign lesions; histopathology is important for ensuring diagnosis and deciding management, particularly for malignant diseases.